Proyecto de factibilidad para la creación de una empresa productora de pollos asados en horno de barro y su comercialización en la ciudad de Loja - Guanuche Andrade, Manjury Cristina (2016)
This research entitled "Feasibility Project for the Creation of a company producing roast chicken in a clay oven and its commercialization in the city of Loja" whose overall objective was to determine the feasibility of creating it. As well as their specific objectives, the same that started with market research; for which we proceeded to apply 397 household surveys in the city of Loja and was also required the application of 50 surveys from local producers and marketers of like product in this city, to determine the supply, demand and marketing and thus constitute the unmet demand for the product that the company claims to offer. Similarly it was necessary to determine the production process that have the roast chicken processing in clay oven, and the estimated time that each activity will require. Once the production process is finished, we proceeded to estimate the company's installed directly related to the number of workers who will work in the production process and the ability of the machine to pack every product capacity. Same resulting elaborate 32,00 chickens daily. Then based on the installed capacity we proceeded to determine the ability to use which was set to begin using the 84% of installed capacity, increasing production gradually each year at a rate of 2% to reach 92% capacity installed, considering the respective maintenance to be given to the machine. The location of the plant according to the results of the mathematical method for the location of the company, gave us as a more likely outcome in the downtown area of the city of Loja, for greater accessibility to the product. The technical study could determine the human and material needed to produce the product, this study allowed to continue with the administrative study which states that the legal base of the company will be established as company liability limits, posing as duration of the company for five years, who are its partners, after that the hierarchical levels of the company, formed as follows, where the main authority is the General Meeting, the manager then followed the counsel, secretary established , accountant, production manager and workers by establishing what their roles and responsibilities within the company will be. We continued financial evaluation presents the following results; The investment of this project is $ 91,927.70; according to the NPV of this project gives us a positive value of $ 111,237.44, indicating that the project is desirable, the IRR is 19.992% and this satisfactory value for the project, the time required for recovery capital would be 3 years 0 months 14.51 days, the sensitivity values are less than one, thus not affecting the project changes increased costs 0.036% and a decrease in revenues by 0.0256 % respectively; the cost - benefit is included for every dollar of investment income of 0.40 cents will be obtained; to reach breakeven in Year I, should produce roast chicken 3564.68 units to break even; likewise it should reach sales of $ 86,722.77, this means that the project is sensitive to these changes. Among the most significant findings and recommendations we have to be the feasible project implementation recommended by the results of the analysis of supply and demand. Being a product known in the market are recommended a strong advertising and promotional campaign in order to raise awareness of the new product.